Pengaruh Naungan Sarang terhadap Persentase Penetasan Telur Penyu Lekang (Lepidochelys olivacea) di Pantai Samas Bantul, Yogyakarta - Rofiah, Amalia; Hartati, Retno; Wibowo, Edy (977-2407769)
The reduced population of sea turtles among other things caused by natural changes in the vicinity of the egg-laying habitat, theft of sea turtle eggs, the utilization of a body part sea turtles by human beings (as the utilization of carapace, meat, bones, and sea turtle eggs), and management of the conservation techniques are inadequate. Pantai Samas Bantul, Yogyakarta, one of the places that are often encountered of Olive Ridley turtle (Lepidochelys olivacea). The aim of this research is to find out the influence of a shade from the success of hatching the eggs of Olive Ridley turtle (Lepidochelys olivacea) in semi natural nest in Samas Beach. The research method used is an experimental method. Observations in the field carried out in June-August 2010. The research was done at the three nests. They are in natural nest, semi natural nest with the shade of zinc, and semi natural nest with the shade of tarpaulin. The results showed the temperature of the nest in the depth of thirty-eight centimeters at the semi natural nest with the shade of tarpaulin about 31,6-31,9 ºC, in the semi natural nest with the shade of zinc about 31,4-31,7 ºC, and in the natural nest is around 31,5-32,3 ºC. The highest moisture is in the natural nest around 6,6 %, while the lowest moisture is in the natural nest with the shade of zinc around 1,5-2,1%. Hatching succes in natural nest is 60 %, semi natural nest with the shade of tarpaulin about 24 %, in the semi natural nest with the shade of zinc about 21 %. The composition of the size of grains of sand in a natural or semi natural nest is dominated by medium-size. Based on the results of research can be concluded that the percentage of hatching the egg of Olive Ridley turtle in the semi natural nest with the shade of tarpaulin is higher than semi natural nest with the shade of zinc, while in the natural nest having the highest percentage of hatching.